Determination of optimum rate and spray frequency of Indoxacarb insecticide for the management of Chickpea bollworm (Helicoverpa armigera) in Eastern Amhara, Ethiopia - Kassaw, Admasie; Mihretie, Aderajew; Tiruneh, Abiye; Mohamed, Awol (International Journal on Food, Agriculture and Natural Resources, 2025)
Bollworm is the major insect pest of Chickpea in Ethiopia. Field experiment was conducted at Sirinka and Cheffa research sites during 2022 main growing season to determine the appropriate rate and spraying frequency of Indoxacarb insecticide and select cost-effective management options of bollworm. A randomized complete block design was implemented with three replications. The combination of three rates and three spraying frequencies of indoxacarb insecticide and unsprayed treatments was evaluated. The lowest (0.27 and 0.03) mean larva number were scored from plots treated 0.75 L with three times spraying frequency at Sirinka and Cheffa respectively. The lowest (1606 and 1269 kg ha-1) chickpea seed yield was found from untreated control plots. Similarly, the highest (2956 and 2835 kg ha-1) seed yield was obtained from plots treated with 0.75 L rates with two and three times spraying frequencies at Sirinka and Cheffa respectively. However the highest (804.4%) marginal rate of return was obtained from plots treated 0.5 L with two times spraying. Generally, 0.5 liter with two times spraying of indoxacarb was effective in controlling bollworm and got the highest cost-benefit advantage as compared with other treatments. Therefore, it could be recommended for the management of chickpea bollworm in the study areas and similar agro-ecologies of chickpea growing areas in Ethiopia.